Learning Assistance Program through puzzles to Improve Students' Arabic Language Skills - Falah, Saiful; Rizal Mz, Syamsul; Fahmi, Nurul; Ahmad Riva’i, Fuad (Rayah Al-Islam, 2024)
This community service program strives to make Arabic language learning more effective and successful by utilizing Arabic sentence puzzle media. This activity employs the notion of Participatory Action Research (PAR), specifically combining research, education, and action with people who actively participate in the service activity process. This service activity involved 51 students from Thamavitya Mulniti School's Smart Arabic classes VIII and IX in Thailand. This service activity will be carried out from August to September 2024. As a result of this activity, students demonstrated excellent participation in Arabic learning, with an average evaluation score of 93.90, a median score of 95 and a frequently occurring score (mode) of 100. There were six students received a score between 80 and 85.6. eleven students who had scores ranging from 85.6 to 91.2. fourteen students received scores ranging from 91.2 to 96.8, while 23 received scores between 96.8 and 100. This is due to the fact that puzzle media requires students to learn both visually and tactically. Additionally, group learning enables students to collaborate and share knowledge with one another. Program pengabdian kepada masyarakat ini bertujuan untuk menjadikan pembelajaran bahasa Arab yang efektif dan berhasil dengan menggunakan bantuan media puzzle kalimat bahasa Arab. Kegiatan ini menggunakan konsep Participatory Action Research (PAR) yaitu sebuah Penelitian Tindakan Partisipatif dengan menggabungkan penelitian, pendidikan, dan aksi dengan subjek yang berpartisipasi aktif selama proses kegiatan pengabdian. Subjek dalam kegiatan pengabdian ini adalah 51 siswa kelas VIII dan IX kelas Smart Arabic di Thamavitya Mulniti School, Thailand. Kegiatan pengabdian ini dilakukan pada bulan Agustus hingga bulan September 2024. Hasil dari kegiatan ini, para siswa mampu mengikuti pembelajaran bahasa Arab dengan sangat baik dengan hasil evaluasi nilai rata-rata sebesar 93,90 dengan nilai tengah 95 dan nilai yang sering muncul (modus) sebesar 100. Siswa yang mendapatkan nilai 80 sampai 85,6 sejumlah 6 orang, siswa yang mendapatkan nilai 85,6 sampai 91,2 sebanyak 11 siswa. 14 orang siswa mendapatkan nilai 91,2 sampai 96,8 dan 23 siswa mendapatkan nilai 96,8 sampai 100. Hal ini dikarenakan media puzzle memfasilitasi siswa bukan hanya belajar melalui visual namun juga taktis. Selain itu, pembelajaran berkelompok juga memungkinkan siswa untuk berkolaborasi dan berbagi pengetahuan satu sama lain.